Efektifitas Daya Hambat Minyak Nabati Terhadap Pertumbuhan Koloni Beberapa Patogen Terbawa Benih Cabai Secara In Vitro - Syamsudin Syamsudin; Satriyas Ilyas; Diah Manohara; Sudarsono Sudarsono (Fakultas Pertanian, Universitas Syiah Kuala, 2007)
Effectiveness of In Vitro Inhibitor Effects of Botanical Pesticides on Growth of Some Pepper Seed Born Pathogens ColoniesABSTRACT. Recently, the use of bio-pesticides significantly increases to control some plant diseases due to the drawback of chemical pesticides to environment. Some experiment have been done to evaluate the effectiveness of some vegetable oil as bio-pesticides to inhibit the colony growth of pepper seed born pathogens in vitro. Various concentrations of vegetable oil were added onto potato dextrose agar medium (PDA), afterward, the growth of pathogen colony in treatment was compared to control (medium without vegetable oil). Evaluation was done in certain period time depend on the growth of every pathogen colony Among the vegetable soil tested, clove oil and Andropogon nardus oil showed a very high inhibitory effect to colony growth of P. capsici, C. capsici, F. oxyporum, R solani, and S. rolfsii. Concentration 0.01% of those oil already inhibited the colony growth of all pathogens more than 75%, with the exception of A. nardus oil which required 0.03% to inhibit C. capsici colony. Concentration of clove and A. nardus oil above 0.01% completely inhibited growth of all pathogens colonies, except for F. oxyporum. Meanwhile, others vegetable oil like Curcuma xanthorrhiza, Kaempferia galangal, Kaempferia pandurata, and Curcuma domestica oil have a low inhibitory effect on growth of all pathogens colonies. To get inhibitory effect more than 75% on the growth of colonies, those vegetable oil needed concentration higher than 0.02%. However, K. galangal and C. domestica required 0.02% oil concentration for P. capsici and S. rolfsii, respectively.